Radiosensitivity index predicts for survival with adjuvant radiation in resectable pancreatic cancer. Issue 1 (October 2015) - Strom, Tobin; Hoffe, Sarah E.; Fulp, William; Frakes, Jessica; Coppola, Domenico; Springett, Gregory M.; Malafa, Mokenge P.; Harris, Cynthia L.; Eschrich, Steven A.; Torres-Roca, Javier F.; Shridhar, Ravi
Abstract Background and purpose Adjuvant radiation therapy for resectable pancreatic cancer remains controversial. Sub-populations of radiosensitive tumors might exist given the genetic heterogeneity of pancreatic cancers. We evaluated whether RSI is predictive of survival in pancreatic cancer treated with radiation. Materials and methods We identified 73 genomically-profiled pancreas cancer patients treated with upfront surgery between 2000 and 2011 (48 radiation, 25 no radiation). Briefly, RSI score is derived from the expression of 10 specific genes and a linear regression algorithm modeled on SF2 of 48 cancer cells. The primary endpoint was to assess the association of RSI with overall survival. Results Median follow-up was 67 months for surviving patients. On multivariate analysis, patients with radioresistant tumors had a trend toward worse survival (Hazard ratio [HR] 2.1 [95% CI 1.0–4.3], p = 0.054). Among high-risk, irradiated patients (positive margins, positive lymph nodes, or a post-operative CA19-9 >90; n = 31), radiosensitive patients had significantly improved survival compared with radioresistant patients (median 31.2 vs. 13.2 months; HR 0.42 [0.19, 0.94], p = 0.04). Among irradiated patients (n = 48), low-risk patients lived longer than both high-risk patients with radiosensitive tumors and radioresistant tumors (HR 2.7 [1.0, 7.2], p = 0.04 and HR 6.3 [2.3, 17.0], p < 0.001, respectively). Conclusions Integrating RSI with standard high-risk variables has the potential to refine the classification of high-risk resected pancreatic cancer patients treated with radiation therapy.